Association and functional analysis of angiotensin-converting enzyme 2 genetic variants with the pathogenesis of pre-eclampsia - Huang, Gongchen; Wang, Yukun; Qin, Linyuan; Huang, Bo; Yu, Xiangyuan (Frontiers in Endocrinology, 2022)
Objective: To investigate the relationship between potential functional single-nucleotide polymorphisms (SNPs) of the angiotensin-converting enzyme 2 (ACE2) gene and the pathogenesis of pre-eclampsia (PE) in Guangxi, China. Materials and methods: A case-control study was conducted involving 327 PE cases and 591 age-matched, normal, singleton pregnant women. Potential functional ACE2 gene variants (rs2106809 A>G, rs6632677 G>C, and rs2074192 C>T) were selected and genotyped using kompetitive allele-specific PCR. The strength of the associations between the studied genetic variants and the risk of PE were evaluated using odds ratios (ORs) and corresponding 95% confidence intervals (CIs). Result: After adjusting for age and body mass index (BMI), unconditional logistic regression analysis showed that rs2106809 A>G was significantly associated with PE risk (AG vs. AA, OR=1.43, 95% CI=1.03–1.99, P=0.034; AG/GG vs. AA, OR=1.45, 95% CI=1.06–1.99, P=0.019), especially with severe PE (AG vs. AA, adjusted OR=1.70, 95% CI=1.10–2.61; AG/GG vs. AA, adjusted OR=1.71, 95% CI=1.14–2.57). Further stratified analysis showed that rs2106809 was even more pronounced in subjects in the pre-BMI >23 kg/m2 (adjusted OR=2.14, 95% CI=1.32–3.45) and TG >2.84 mmol/L subgroups (adjusted OR=1.81, 95% CI=1.09–3.01) under the dominant genetic model. We also found that rs2106809 interacted with pre-BMI (Pinteraction=0.040), thereby affecting an individual's genetic susceptibility to PE. Multiple dimension reduction analysis demonstrated that rs2106809 made the best one-locus model, and the three-locus model was the best interaction model for predicting PE risk. Functional analysis suggested that rs2106809 A>G causes a change in the reliability of classifications of two putative splice sites in the ACE2 gene, potentially regulating the expression of functional genes (PIR, ACE2, and CLTRN) in multiple tissues and cell lines (P<0.05). Conclusion: The ACE2 gene rs2106809 A>G variant is significantly associated with the risk of PE via individual locus effects and/or complex gene-gene and gene-environment interactions. Regulating the expression of functional genes such as PIR, ACE2, and CLTRN may be the molecular mechanism by which rs2106809 increases an individual’s susceptibility to PE.